Influência do controle droop sobre o perfil de tensão em um alimentador com geração distribuída - Pazdiora, Jonathan Rodrigo (2019)
The increase in the generation of electric energy, such as wind and photovoltaic, installed in the distribution systems, has caused considerable changes in the way these systems operate. Traditionally, distribution systems consider the unidirectional power flow, and the voltage control strategies, through capacitor banks and voltage regulators, follow the same assumption. Thus, introducing distributed generators in the system causes changes in the voltage profile (sub or overvoltage), establishing one of the main technical impacts in steady state voltage, and making it necessary to evaluate methods that can mitigate the effects caused by the penetration of new sources and forms of electric power generation. The voltage droop control is among these methods, which has the potential to mitigate the effects of distributed generators on the voltage profile, taking advantage of such functionality in generators that are connected through inverters. The present dissertation deal with the influence of voltage droop control for generators installed in a feeder of the distribution system, relating its effects with usual electrical characteristics and voltage sensitivity to both active and reactive power injections. The study is carried out by connecting an inverter based distributed generator to a 13,8kV, 60Hz, distribution feeder, considering the generator operating with and without voltage droop control. The analysis considers the steady state voltage along the feeder, the voltage sensitivity, and the penetration index. The obtained results, through the computational simulations carried out, show that the voltage droop control brings significant improvements to the voltage profile of the feeder. and allows to verify its influence in relation to other characteristics of the system, as well as its control variables. Thus, adjustments can be made that can result in power quality gains.